2017
DOI: 10.1039/c6dt04714a
|View full text |Cite
|
Sign up to set email alerts
|

The key role of the composition and structural features in fluoride ion conductivity in tysonite Ce1−xSrxF3−x solid solutions

Abstract: Pure tysonite-type CeSrF solid solutions for 0 ≤ x < 0.15 were prepared by a solid-state route at 900 °C. The cell parameters follow Vegard's laws for 0 ≤ x ≤ 0.10 and the solubility limit is identified (0.10 < x < 0.15). For 0 ≤ x ≤ 0.05, the F2-(Ce,Sr) and F3-(Ce,Sr) bond distances into [CeSrF] slabs strongly vary with x. This slab buckling is maximum around x = 0.025 and strongly affects the more mobile F1 fluoride ions located between the slabs. The F MAS NMR spectra show the occurrence of F1-F2,3 exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 62 publications
5
37
0
5
Order By: Relevance
“…[295] This technique achieved ah igh ionic conductivity comparable to that of the single-crystal samples.T he microstructural study indicated that the F1 site (Figure 21 a) with the anion vacancies is the main contributor to fluorine mobility.T he same group used as imilar method to prepare solid solutions of the pure tysonites Sm 1Àx Ca x F 3Àx and Ce 1Àx Sr x F 3Àx ,w hich possessed the highest room-temperature ionic conductivities of 1 10 À4 and 3 10 À4 Scm À1 for the optimum compositions of Sm 0.95 Ca 0.05 F 2.95 and Ce 0.975 Sr 0.025 F 2.975 ,r espectively. [296,297] However,t heir application in the full battery is limited by their mechanical incompatibility with electrode powder materials.…”
Section: Fluoride-ion Batteriesmentioning
confidence: 99%
“…[295] This technique achieved ah igh ionic conductivity comparable to that of the single-crystal samples.T he microstructural study indicated that the F1 site (Figure 21 a) with the anion vacancies is the main contributor to fluorine mobility.T he same group used as imilar method to prepare solid solutions of the pure tysonites Sm 1Àx Ca x F 3Àx and Ce 1Àx Sr x F 3Àx ,w hich possessed the highest room-temperature ionic conductivities of 1 10 À4 and 3 10 À4 Scm À1 for the optimum compositions of Sm 0.95 Ca 0.05 F 2.95 and Ce 0.975 Sr 0.025 F 2.975 ,r espectively. [296,297] However,t heir application in the full battery is limited by their mechanical incompatibility with electrode powder materials.…”
Section: Fluoride-ion Batteriesmentioning
confidence: 99%
“…Recently, several studies concerning various anode [20,21] and cathode materials [22] appeared; their suitability and performance have always been investigated in combination with La0.9Ba0.1F2.9 as the ceramic electrolyte of choice. To the best of our knowledge, no detailed studies concerning the electrochemical stability of solid-state fluoride electrolytes against metallic current collectors have been reported yet, neither of La0.9Ba0.1F2.9 nor of other F conductors such as Ba0.7Sb0.3F2.3, which is not stable against Ce as anode material [23], Ce1xSrxF3x (0 ≤ x < 0.15) [24] or Sm1xCaxF<...>…”
Section: Introductionmentioning
confidence: 99%
“…Die gleiche Gruppe verwendete eine ähnliche Methode, um die Sm 1− x Ca x F 3− x ‐ und Ce 1− x Sr x F 3− x ‐Tysonit‐Mischkristalle zur präparieren, welche die bei Raumtemperatur höchsten Ionenleitfähigkeiten von 1×10 −4 bzw. 3×10 −4 S cm −1 für die optimalen Zusammensetzungen von Sm 0.95 Ca 0.05 F 2.95 und Ce 0.975 Sr 0.025 F 2.975 besaßen . Allerdings ist ihre Anwendung in der aufgeladenen Batterie aufgrund ihrer mechanischen Inkompatibilität mit Elektrodenpulvermaterialien begrenzt.…”
Section: Halogenid‐ionen‐batterienunclassified
“…Aufsätze optimalen Zusammensetzungen von Sm 0.95 Ca 0.05 F 2.95 und Ce 0.975 Sr 0.025 F 2.975 besaßen. [296,297] Allerdings ist ihre Anwendung in der aufgeladenen Batterie aufgrund ihrer mechanischen Inkompatibilitätm it Elektrodenpulvermaterialien begrenzt.…”
Section: Angewandte Chemieunclassified